Patient Experiences Towards Satisfaction in Accessing Examinations HIV/AIDS and ARV Treatment - Nasrianti Nasrianti; Hasnia Hasnia; Tyan Lestari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Puskesmas is a functional organizational unit that carries out health efforts that are comprehensive, integrated, equitable and can be reached and accepted by the community. A service is said to be good by a patient, determined by the fact that the service provided can meet the patient's needs using the patient's perception of the service received (satisfactory or disappointing, also including the length of service time). Patient satisfaction with examination and treatment services for patients with HIV/AIDS in various patient groups at the health service administration level at health centers and hospitals, comfort in using health services including waiting times and administrative procedures. Objective: HIV AIDS patients who undergo examinations and visits to the Sentani Community Health Center. Method: This research is qualitative research with an exploratory phenomenology approach, 3 participants, and the data collection technique is in-depth interviews. Results: The research results found three themes, including understanding about HIV AIDS, obstacles experienced during treatment, and easier access to health services. Conclusion: Health services for patients with HIV/AIDS require education and understanding and accessing health services through comprehensive education and counseling. Patients with HIV/AIDS require special attention in getting appropriate care. Access to complete health services for people with HIV/AIDS requires counseling between health workers aimed at exploring problems in order to find solutions in the resolution process.